2019
DOI: 10.3389/fgene.2019.00817
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Silent Mutation in the L1CAM Gene Causing Fetal Hydrocephalus Detected by Whole-Exome Sequencing

Abstract: X-linked hydrocephalus (XLH), a genetic disorder, has an incidence of 1/30,000 male births. The great proportion of XLH is ascribed to loss-of-function mutations of L1 cell adhesion molecule gene (L1CAM), but silent mutations in L1CAM with pathogenic potential were rare and were usually ignored especially in whole-exome sequencing (WES) detection. In the present study, we describe a novel silent L1CAM mutation in a Chinese pregnant woman reporting continuous five times pregnancies with fetal hydrocephalus. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The present study has 4 major strengths. First, following the advent of WES technology, it has proven to be efficient in unearthing sequence variation across the MAF spectrum in obstetric and gynecological diseases [ 25 , 37 ]. Using this method, we successfully identified novel candidate pathogenicity loci with known functional genes ABCB4 , ABCB11 [ 24 ] and ABCC2 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study has 4 major strengths. First, following the advent of WES technology, it has proven to be efficient in unearthing sequence variation across the MAF spectrum in obstetric and gynecological diseases [ 25 , 37 ]. Using this method, we successfully identified novel candidate pathogenicity loci with known functional genes ABCB4 , ABCB11 [ 24 ] and ABCC2 .…”
Section: Discussionmentioning
confidence: 99%
“…This can omit some potentially pathogenic mutations. Recently, WES technology has proved to be a powerful new approach for detecting low-frequency (0.01 ≤ MAF <0.05) and rare (MAF <0.01) variations that affect human diseases, such as spontaneous preterm birth ( Huusko et al, 2018 ) and fetal hydrocephalus ( Sun et al, 2019 ). Using this method, we have also successfully revealed ANO8 as a genetic risk factor for ICP ( Liu et al, 2020 ) and identified 42 novel mutations in ABC transporter genes that are associated with ICP in 151 samples ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…sanger.ac.uk), OMIM (http://omim.org/), PubMed (http:// www.ncbi.nlm.nih.gov/pubmed), ClinVar (https://www.ncbi. nlm.nih.gov/clinvar/), and HGMD (http://www.hgmd.cf.ac.uk/ ac/index.php) databases were used to investigate the clinical relevance of the mutations (9).…”
Section: Whole Exome Sequencingmentioning
confidence: 99%